PELAKSANAAN KETERAMPILAN DASAR MENGAJAR DOSEN DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI STIK BINA HUSADA PALEMBANG - Maryance, Maryance (Jurnal Pendidikan Guru, 2017)
Lecturers as educators have a lot of teaching skills, it will be easier to motivate student learning in achieving optimal learning results. In connection with the teaching skills must be owned educators, Mardia Conservation stated that there are some basic skills teaching should possess an educator, namely: 1) Skills opening lesson; 2) Skills to ask; 3) Skill provide reinforcement; 4) Skill held variation; 5) Skills to explain; and 6) classroom management skills (Mardia Conservation, 2008: 204). From teaching some basic skills that should be possessed by an educator above, it is clear that the duty to teach for an educator is not an easy task. Teaching is to guide student activities, arranging and organizing the environment that is around students so as to encourage and foster the spirit of students for learning activities. This study aims to investigate the implementation of basic skills teaching faculty in the teaching of Islamic Education in STIK Bina Husada Palembang, and to determine the success rate of students from faculty aspect using basic skills teaching faculty in the teaching of Islamic Education in STIK Bina Husada Palembang. This study is qualitative and qualitative method with research informants 3 PAI lecturers and students of Public Health Semester 3 2015/2016 academic year, amounting to 18 people. Data analysis was carried out by means of data reduction, data presentation, conclusion. The results showed that the implementation of basic skills teaching faculty in learning STIK Bina Husada PAI in Palembang is good. This is according to the results of interviews and observations the author of the aspects observed include the skills to explain, questioning skills, skills provide variety of stimulation, skills provide reinforcement, skill opened the lessons and skills to close the lesson, teaching skills of small groups and individuals, and classroom management skills , As for the success rate of students from the aspect of teachers use teaching basic skills in learning STIK Bina Husada PAI in Palembang, among others, in view of the effectiveness, attractiveness, interest, and motivation to learn.